Collimation and focusing of wave beams with metal-plate lens antennas analyzed using nystrom-type MDS algorithm - Nosich, A.A.; Gandel, Y.V.; Matsushima, A.; Sauleau, R. (2008 IEEE Antennas and Propagation Society International Symposium, 2008)
We present a full-wave numerical study and design of the 2-D model of a perfectly electric conducting (PEC) parallel-plate lens structure. The underlining idea is that the power of electromagnetic waves can be focused or collimated by arranging flat metal strips in parallel to one another (for instance, see Fig. 1-a) and adjusting the transverse and longitudinal dimensions of the waveguide regions to provide a necessary phase correction. Simple engineering principles for designing such metal-plate lenses are known from [1-3]. As for the full-wave analysis, they seem to have been accurately considered only in [4] with the coupled Singular Integral Equations (SIEs) regularized by using a projection on the weighted Chebyshev polynomials, which are the orthogonal eigenfunctions of the static parts of the SIE operators.